The welfare economics of public policy a practical approach to project and policy evaluation - Just, Richard E. (2004 E. Elgar)
This outstanding text, a follow-up to the authors' award-winning 1982 text, provides a thorough treatment of economic welfare theory and develops a complete theoretical and empirical framework for applied project and policy evaluation. The authors illustrate how this theory can be used to develop policy analysis from both theory and estimation in a variety of areas including: international trade, the economics of technological change, agricultural economics, the economics of information, environmental economics, and the economics of extractive and renewable natural resources.
Includes bibliographical references (p. 650-671) and indexes.
Keywords: Welfare economics